Some Phytogeographical and Economic Aspects of the Genus Sterculia - Datta, K. (Indian Forester, 1966)
In view of the growing importance of the study and exploitation of Indian resources, it becomes necessary to review the economics of important plants. After careful examination it has been found that the species of Indian Sterculia present an enormous scope of giving substitute and organic products in the growing economy of the country. As such, in this paper, a general distribution of various species of Sterculia has been given, while dealing with different Indian species of the genus. A concise account of the uses of various Indian species is being reviewed, and the ratio between the economical and non-economical species of the genus in the world along with a spectrum showing the uses of the exploited species of India.